VIRTUAL LABORATORY BASED ON INGENHOUSZ EXPERIMENT MODELING: ENHANCING CONCEPTUAL UNDERSTANDING AND SCIENTIFIC LITERACY - Adnan Adnan; Syamsiah Syamsiah; Dian Aswita; Nur Hikmah; Nur Risnawati Kusuma; Sahla Sahira; Muh Yunus (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to evaluate the effectiveness of the Ingenhousz Experiment Virtual Laboratory, integrated with the GENIUS syntax, within a Blended Learning framework to accelerate students' conceptual understanding and science literacy in photosynthesis.Methodology – A quasi-experimental research with a Replicated Experimental Design was employed. The study involved 136 eleventh-grade science students at SMA Negeri 3 Makassar, divided into three experimental replication classes and one control class. Conceptual understanding was measured using a 20-item multiple-choice test, while science literacy was assessed through a 5-item essay test. Data were analyzed using descriptive statistics, N-Gain calculations, ANCOVA, and Least Significant Difference (LSD) post-hoc tests.Findings – Initial assessments indicated equivalent suboptimal cognitive baselines across all groups. Post-intervention, all replication classes demonstrated a profound cognitive escalation, achieving a "High" N-Gain category (0.77–0.89), whereas the control group remained in the "Moderate" category. ANCOVA confirmed a highly significant treatment effect (p = 0.000). LSD tests revealed no significant variance among the three replication classes, but all significantly outperformed the control group, confirming the intervention's consistency and reliability.Contribution – This study provides a replicable pedagogical framework, demonstrating that synergizing structured inquiry syntax with interactive virtual simulations successfully transforms students into active scientific researchers and effectively overcomes the limitations of conventional teaching.